Quantized consensus of finite-level multi-agent networked systems - Nuga, Olubusola Olufunke; Amusa, Kamoli Akinwale; Olanipekun, Ayorinde Joseph; Matthew, Simeon (International Journal of Advances in Applied Sciences, 2024)
In this paper, analysis of a quantized consensus finite-level multi-agent networked system is considered. Logarithmic quantizer is utilized for the transmission of the state of the networked agents. Two protocols employed in the investigation are, the consensus protocol which is determined from the outputs and states of a set of encoder-decoder pair, and the convergence rate protocol that is precisely characterized using a dynamic scaling factor. The asymptotic consensus can be reached through information exchange among neighbour agents. Validity of the protocols for the connected network system is established through careful selection of parameters of the quantizer. A four-agent networked system is used to illustrate the implementation of the protocols. Obtained result showed that information exchange in an undirected networked system is achievable through a communication channel equipped with encoder and decoder pairs. More so, the desired asymptotic convergence is achievable through careful choice of the parameters of the quantizer.